Analysis of the Implementation of a Deep Learning Approach Assisted by Concrete Media for Fifth Grade Elementary School Students - Rika Arfiyani; Herlina; Sisriawan Lapasere; Zulnuraini; Sri Wahyuni (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to describe the application of a deep learning approach supported by concrete media among fifth-grade students at SDN II Puntari Makmur. The method used was descriptive qualitative, with the research subjects involving fifth-grade students and the fifth-grade teacher at SDN II Puntari Makmur. The research instruments consisted of observation, interviews, and documentation, as well as data analysis through data collection, data condensation, data presentation, and drawing conclusions. The results of the study indicate that the implementation of a deep learning approach supported by concrete media in teaching the geometry unit in fifth grade at SDN II Puntari Makmur was successfully carried out and demonstrated achievement across all deep learning indicators: mindful learning, meaningful learning, and joyful learning. Among all the achieved indicators, regarding the aspect where students can rephrase the material in their own words under the meaningful learning indicator, further reinforcement is still needed to encourage students’ courage to ask questions and their ability to communicate their understanding in a more complex manner. The use of concrete media such as interactive flat panels (IFPs), geometric measuring tools, and real-world objects also facilitated the achievement of all deep learning indicators.